2017
DOI: 10.3329/pa.v28i1.32851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yield and yield contributing traits for submergence tolerance of rice

Abstract: Ten rice genotypes were evaluated for association studies of yield and its contributing traits to select the traits for yield improvement in submerged condition. An experiment was conducted in the experimental field of Bangladesh Institute of Nuclear Agriculture (BINA) and 15 morphological traits Viz. Days to flowering (days), plant height (cm), Tiller number plant-1 , (Nos.), effective tiller number plant-1 (Nos.), 100 seed weight (g), harvest index (%) etc. were studies to measure nature of  association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Sari et al (2019) and Akshaya (2020) reported that the plant height on grain yield had a high positive indirect effect through flag leaf length. However, Afrin et al (2017) reported negative indirect effects through days to fifty50 per cent flowering, panicle length, plant height and the number of productive tillers per plant.…”
Section: Rajasekar Et Almentioning
confidence: 98%
“…Sari et al (2019) and Akshaya (2020) reported that the plant height on grain yield had a high positive indirect effect through flag leaf length. However, Afrin et al (2017) reported negative indirect effects through days to fifty50 per cent flowering, panicle length, plant height and the number of productive tillers per plant.…”
Section: Rajasekar Et Almentioning
confidence: 98%
“…Traits such as RI, AVI, AGP, SL, RL, and HSW had a high genetic advance as a percentage of mean (GAM) coupled with high heritability. High heritability plus high genetic advance would be the best genotype selection indicators ( Afrin et al., 2017 ). Thus, these traits should be given highest priority in improving anaerobic germination potential during crop breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…It highlighted the potential of low-cost methods to increase flood tolerance and productivity in flood-prone regions. Afrin et al, (2017) evaluated morphological and production traits in submergedtolerant rice genotypes, identifying traits positively correlated with production. It suggested breeding submerged-tolerant rice genotypes as a promising approach for improving yield.…”
Section: Literature Reviewmentioning
confidence: 99%